1988
DOI: 10.1111/j.1530-0277.1988.tb01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime Ethanol Increases Resistance of Upper Airways and Produces Sleep Apneas in Asymptomatic Snorers

Abstract: Nasal continuous positive airway pressure (nasal CPAP) and polysomnography were used to analyze the time course of the effect of bedtime ethanol on resistance of upper airways and on the number of respiratory pauses during sleep. On one night, six asymptomatic nonalcoholic male snorers drank 2 ml/kg of 100 proof vodka mixed in orange juice (ethanol dose, 0.79 gm/kg, giving a peak blood alcohol level of 71.8 +/- 33.3 mg/dl). On a second night they received a placebo (1-2 drops of vodka floated on top of the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
3
12

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 18 publications
0
67
3
12
Order By: Relevance
“…This was equally true of subjects with mild and severe OSAS, and was also true for the first 2 h, when the blood alcohol level would have been highest. This result conflicts with the findings of MITLER et al [12], who found a small increase in the pressure required to prevent snoring in nonapnoeic snorers, but is compatible with the results of BERRY et al [16], who found that there was no change in the AHI or Sa,O 2 with alcohol in subjects who were already on adequate CPAP. One possible explanation is that in patients with frank OSAS, as opposed to snoring, the upper airway is already almost totally floppy during sleep, and the existing pressure used for CPAP provides nearly all of the inspiratory support.…”
Section: Pressure Requirementcontrasting
confidence: 57%
See 3 more Smart Citations
“…This was equally true of subjects with mild and severe OSAS, and was also true for the first 2 h, when the blood alcohol level would have been highest. This result conflicts with the findings of MITLER et al [12], who found a small increase in the pressure required to prevent snoring in nonapnoeic snorers, but is compatible with the results of BERRY et al [16], who found that there was no change in the AHI or Sa,O 2 with alcohol in subjects who were already on adequate CPAP. One possible explanation is that in patients with frank OSAS, as opposed to snoring, the upper airway is already almost totally floppy during sleep, and the existing pressure used for CPAP provides nearly all of the inspiratory support.…”
Section: Pressure Requirementcontrasting
confidence: 57%
“…Potentially, alcohol consumption might be expected to change the continuous positive airway pressure (CPAP) requirements for the treatment of OSAS [2,12,16]. MITLER et al [12] showed that 2 mL·kg -1 BW vodka produced a significant increase in the pressure required for CPAP from 4.8 to 6.2 cmH 2 O.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, ethanol promotes relaxation of the muscles of the upper airways, increasing the resistance of the upper airways and can lead to obstructive sleep apnea (OSA). Additionally, intake of alcohol can prolong the duration of apnea, suppress awakenings, increase the frequency of occlusive episodes and worsen the severity of hypoxemia [23][24].…”
Section: Neurology and Neuroscience Issn: 2386-687xmentioning
confidence: 99%